Triage and Protocol Recommendations for the Parasitology Laboratory Based on an Epidemiological Investigation of Parasite Diagnostics in Ontario Laboratories - Allison Maier; Julia Krolik; Anna Majury (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVES:A study was performed using a subset of Ontario laboratory parasitology data, with three objectives: to describe parasitic infections in Ontario; to identify risk factors for acquiring a parasitic infection using routinely collected information; and to use this information to assess current protocols for parasite testing in laboratories and, in turn, to propose alternatives to optimize the allocation of laboratory resources.